ダイ 25 ジ ナンキョク チイキ カンソク タイ ナイリク チョウサ オヨビ リョコウ ホウコク - 藤井, 理行; フジイ, ヨシユキ; 川田, 邦夫; カワダ, クニオ; 吉田, 稔; ヨシダ, ミノル; 松本, 慎一; マツモト, シンイチ; 谷崎, 政弘; タニザキ, マサヒロ; 原, 達夫; ハラ, タツオ; et al. (1985)
P(論文) 第25次南極地域観測隊越冬隊は, 東クィーンモードランド地域の内陸調査旅行を, 1984年10月から1985年1月までの3ヵ月間, 8名の隊員で延べ2500kmの規模で実施した。この調査旅行は, 「東クィーンモードランド地域雪氷・地学研究計画」(第23-29次観測隊, 雪氷計画は27次観測隊まで)の一環を成すもので, 氷床最内陸部での雪氷, 気象観測と, 今後の内陸構想の拠点としての前進キャンプの設置を主な目的として計画された。調査旅行は, 4台の雪上車を用いてすすめられ, 一等基本観測地点4ヵ所での氷床流動と歪の再測, 再測を要しない雪氷観測を行う二等基本観測地点5ヵ所の設置, ルート沿いの観測などを実施したほか, 11月21日には南緯74°12′02″, 東経34°59′08″, 標高3193m地点に前進キャンプを設置した。11月23日, 前進キャンプから約90km南下した地点で, 昭和基地へ旅行隊の医者を早急に送り返す必要が生じたため, 越冬隊長から旅行を中止するよう命令が出され, これに従った。ここでは, 内陸調査旅行の報告として, 行動経過, 調査, 設営それぞれの概要を述べる。 The 25th Japanese Antarctic Research Expedition (JARE-25) carried out an inland glaciological traverse as the third-year field work for the East Queen Maud Land Glaciological Project (EQGP) from October 1984 to January 1985. A eight-man party including four glaciologists conducted the traverse over 2500km in distance using four oversnow vehicles and 16 2t-sledges. During the traverse, four strain-grid stations, G1 (71.4°S, 43.7°E), G6 (73.1°S, 39.8°E), G7 (73.7°S, 39.8°E) and G15 (71.2°S, 46.0°E), were resurveyed. Positioning (JMR 4A), surface elevation determination, surface slope, gravity, ice thickness (radio echo sounding), installation of offset markers, 10-m ice coring and 10-m snow temperature measurement were carried out at other five glaciological grid points. An advance camp was established at 74°12′02″S, 34°59′08″E and 3193m a. s. l. on October 21,1984 for future inland activities. In addition to strain grid installation and satellite positioning a glaciological work as was made at grid points was carried out at the advance camp. Unmanned meteorological observation at the camp was started with ARGOS system using NOAA-7,-8 and the data have been sent in good condition to Japan via CNES, France. departmental bulletin paper